DOES INTENTION MATTERS FOR BMT MEMBER TO INVEST IN MUDHARABAH MUQAYYADAH DEPOSIT? : The Case of BMT Under Indonesia Sharia Cooperative Association (AKSYINDO) - Priyadi, Rohman; Ismal, Rifki; Rahman, Arip (Airlangga International Journal of Islamic Economics and Finance, 2024)
Baitul Mal wat Tamwil (BMT) plays an important role in collecting and managing funds, as well as channeling them to mikor business actors with the principles of justice that are free from usury. However, it was found that members' interest in investment products in cooperatives is still relatively low. This study aims to analyze the intention of BMT members to invest in mudharabah muqayyadah savings by using the Theory of Planned Behaviour (TPB). The sampling method uses cluster random sampling by distributing online questionnaires to all investors in muqayyadah mudharabah deposits whose BMTs are registered with Aksyindo. Data from 191 respondents were analyzed by using SmartPLS 3.2.9 Structural Equation Modeling. This research was found that all intention determinant variables in TPB namely attitude, subjective norms and perceived behavioral control have positive and significant effects on the intention to invest in muqayyadah mudharabah savings, while other observed variables, namely knowledge, religious factors, risk and return, and sharia compliance have positive and significant effects on attitudes in investing in muqayyadah mudharabah savings. Based on the findings of this study, it is concluded that the BMT needs to improve the factors that influence the intention to invest in muqayyadah mudharabah savings in order to overcome the problem of low interest in investing in muqayyadah mudharabah savings. This study can be a consideration for regulators and practitioners to design effective strategies in developing the Islamic financial industry, especially BMTs that are developing in Indonesia.